ANALYSIS OF EMOTIONAL INTELLIGENCE, STRESS, AND STYLES OF PARTICIPATIVE LEADERSHIP EFFECT TO WORK SATISFACTION IN IMPROVING PERFORMANCE OF EMPLOYEES PT. WASKITA BETON PRECAST Tbk. - Kusumo, Rio Radityo (Master of Management Diponegoro University, 2018)
The purpose of this study was to analyze the influence of emotional intelligence, stress and participative leadership style to employee performance with job satisfaction as mediation. This research type is explanatory research. Population and sample in this research are all employees of the marketing department of PT. Waskita Beton Precast totaling 112. The method of data collection questionnaire. The data type is the primary data. The method of data collection is the questionnaire. Data analysis technique used is the structural equation model. The results showed that: 1). Emotional intelligence has effect positive and significant on job satisfaction. 2). Stress has an effect negative and significant on job satisfaction. 3). Participatory leadership style has effect positive and significant on job satisfaction. 4). Job satisfaction has effect positive and significant on employee performance. 5). Emotional intelligence has effect positive and significant on employee performance. 6). Stress has an effectÂ negative and significant on employee performance. 7). Participative leadership style has effect positive and significant on employee performance